Pengaruh Diskon, Gratis Ongkir, dan Online Customer Review terhadap Keputusan Pembelian Produk Fashion di Shopee pada Masyarakat DKI Jakarta - Stevanus Stevanus; Nadya Nadya Fadillah F; Prima Andriani (Indo Publishing, 2026)
This study aims to analyses the influence of discounts, free shipping, and online customer reviews on purchasing decisions for fashion products on Shopee among the people of DKI Jakarta. This research employed a quantitative approach using a survey method. The sample consisted of 130 respondents selected through purposive sampling. Data were collected using an online questionnaire distributed via Google Forms and analyzed using multiple linear regression with IBM SPSS. The results indicate that discounts, free shipping, and online customer reviews each have a positive and significant effect on purchasing decisions, with significance values below 0.05. Simultaneously, the three independent variables also have a positive and significant effect on purchasing decisions, with an F-value of 817.331 and a significance value of 0.000 (p < 0.05). The Adjusted R Square value of 0.926 indicates that 92.6% of the variation in purchasing decisions is explained by discounts, free shipping, and online customer reviews, while the remaining 7.4% is influenced by other variables not examined in this study. In conclusion, discounts, free shipping, and online customer reviews significantly influence purchasing decisions for fashion products on Shopee among the people of DKI Jakarta.